2022
DOI: 10.1038/s41598-022-09068-1
|View full text |Cite
|
Sign up to set email alerts
|

On the durability of surgical masks after simulated handling and wear

Abstract: After the spread of COVID-19, surgical masks became highly recommended to the public. They tend to be handled and used multiple times, which may impact their performance. To evaluate this risk, surgical masks of Type IIR were submitted to four simulated treatments: folding, ageing with artificial saliva or sweat and washing cycles. The air permeability, mechanical integrity, electrostatic potential, and filtration efficiency (FE) of the masks were measured to quantify possible degradation. Overall, air permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
(14 reference statements)
5
14
1
Order By: Relevance
“…Cotton and PP fibres appear in a few publications with different applications under dynamic loading 27 . The durability of face masks in handling and wear has been given by Varanges et al 28 . The effect of the mechanical behaviour of each mask was assessed in its strain or stretching behaviour during wearing.…”
Section: Resultsmentioning
confidence: 99%
“…Cotton and PP fibres appear in a few publications with different applications under dynamic loading 27 . The durability of face masks in handling and wear has been given by Varanges et al 28 . The effect of the mechanical behaviour of each mask was assessed in its strain or stretching behaviour during wearing.…”
Section: Resultsmentioning
confidence: 99%
“…Filter-based antimicrobial technologies have been developed to inhibit the airborne transport of bioaerosols and related exposure [ 354 , 355 ]. The degradation of the performance of PPE and air-cleaning systems is also an important factor for exposure assessment [356][357][358][359][360][361] .…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…The difference is the case in Europe and America, but the trend has changed and wearing a protective face mask has become a natural part of our lives in recent months. The authors of the manuscript [6] subjected surgical face masks to four simulated cycles of folding, aging with artificial saliva, or sweating and washing. They concluded that folding, saliva and sweat have little effect on the face mask's effectiveness and aging (depreciation).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that folding, saliva and sweat have little effect on the face mask's effectiveness and aging (depreciation). Research has confirmed that one can wear a worn surgical face mask longer than usual, the recommended four hours [6]. The pathogens have lived with us since time immemorial, so it is appropriate to introduce prevention and prevent infection.…”
Section: Introductionmentioning
confidence: 99%